Incidence of maple syrup urine disease, propionic acidemia, and methylmalonic aciduria from newborn screening data - Chapman, Kimberly A.; Gramer, Gwendolyn (Molecular genetics and metabolism reports, 2018)
Incidence for the branched-chain intoxication-type disorders, maple syrup urine disease, propionic acidemia and methlymalonic aciduria is dependent on the population screened. Here newborn screening results from three world regions, state screening laboratories in the United States, a region in Germany and Kuwait provides new incidence numbers. Maple syrup urine disease incidence in the United States was calculated to be 1: 220219, in South-West Germany 1: 119573 (Germany nationwide 1:177978), and in Kuwait 1: 59426. Incidence of propionic acidemia alone is calculated to be 1: 242741 in the United States, 1: 284450 in South-West Germany (Germany nationwide 1:202617) and 1:59426 in Kuwait. Incidence of isolated methylmalonic aciduria alone is 1:69354 in the United States, 1:568901 in South-West Germany (Germany nationwide 1:159199) and 1: 19809 in Kuwait. In the United States several newborn screening laboratories combine their results for propionic acidemia and methylmalonic aciduria, and also include combined remethylation disorders in the respective category, resulting in an incidence of 1:50709. Combined evaluation of methylmalonic aciduria, propionic aciduria and combined remethylation disorders results in a similar incidence for Germany of 1:67539. This evaluation of newborn screening incidences reflects some population differences for three intoxication-type metabolic disorders. However, different sample sizes of the populations screened over different time periods, and differences in case definitions for methylmalonic acidurias have to be considered when interpreting these data.
Available online 5 April 2018
Gesehen am 10.04.2019